Small scale poultry farmers’ choice of adaption strategies to climate change in Ogun State, Nigeria (2018)
Climate risks constitute an enormous challenge to poultry production and have affected the livelihoods of the people who depend on them. Thus, farmers have adopted various strategies that can help them cope with the adverse effects of climate change. The aim of this study is to examine the factors influencing small scale poultry farmers’ choice of adaptation strategies to climate change. Data used for this study were obtained from 121 representative farmers selected through a two-stage random sampling procedure. Descriptive Statistics, Likert Scale and the Multinomial Logit Model were the tools used for analysis. Results showed that the mean age and household size of the respondents were 45 years and 5 persons respectively, while the average number of birds per farmer stood at 583 birds. Majority of the respondents had a moderate perception of the impacts of climate change on poultry farming and chose management adaptation strategies in their fight against climate change. Econometric analysis showed that the age, gender and educational status of farmers, number of birds, household size, poultry experience, access to cooperative societies, poultry housing system, access to credit, access to extension services and farm size were the factors influencing farmers’ choice of climate change adaptation strategies in the study area. Therefore, policy should focus on awareness creation on management adaptation strategies through enhancing education and extension services as well as access of poultry farmers to credit facilities to indirectly insure farmers against climate change impacts.